Peningkatan Hasil Belajar Peserta Didik Melalui Model Pembelajaran Discovery Learning Berbantuan Audio Visual pada Fase D SMPN 19 Surakarta - Agustinus Sucipto (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
This study evaluates the impact of the implementation of the Independent Curriculum at SMPN 19 Surakarta. The focus of the research is on the subjects of Catholic Religious Education and Ethics in grade VIII G Phase D. The implementation of this curriculum presents significant challenges for students and teachers, which requires comprehensive improvements to ensure the effectiveness of education in general, and specifically on the subjects of Catholic religious education and ethics to match the spirit of the Independent Curriculum.In overcoming these challenges, the research proposes a solution in the form of an Audio Visual Assisted Discovery Learning Learning Model. This model has been shown to effectively improve learning outcomes (cognitive) and affective outcomes dimensions Have of faith, Learners on two cycles of research. Affective results showed a significant increase from cycle I to cycle II with an average increase in achievement of 15%. Likewise with learning outcomes, showing an average increase in achievement of 15%. Although the Audio-Visual Assisted Learning Discovery Learning Model has proven effective, researchers recommend further evaluation of the model's implementation in various educational contexts. SMPN 19 Surakarta needs to continue to improve learning strategies, increase student engagement, and pay attention to the readiness of teachers and facilities and infrastructure in order to integrate audiovisual technology. Regular training for teachers and intensive support in teacher empowerment are also needed to ensure the success of education transformation in accordance with the spirit of the Independent Curriculum.